2014
DOI: 10.1117/12.2039893
|View full text |Cite
|
Sign up to set email alerts
|

Laser beams with conical refraction patterns

Abstract: Laser beams with cone-refracted output from the plane mirror is demonstrated for the first time in lasers based on intracavity conical refraction (CR) phenomenon. Transverse profile of such lasers comprises a crescent ring of CR-like distribution, where any opposite points are of orthogonal linear polarizations. We confirm the existence of such mode of CR lasers by two observations. First, cascaded CR in reflection geometry has been demonstrated for first time and it provides experimental prove that a light be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
(28 reference statements)
1
18
0
Order By: Relevance
“…CR has been also considered for technological applications, being at the heart of a single shot novel polarimeter [131,271] and of a solid state laser [138]. In particular, in Chapter 10 of this thesis we have also reported a free space optical communication (FSOC) system for multiplexing and demultiplexing multiple polarization channels with a cascade of 3 biaxial crystals, see Ref.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CR has been also considered for technological applications, being at the heart of a single shot novel polarimeter [131,271] and of a solid state laser [138]. In particular, in Chapter 10 of this thesis we have also reported a free space optical communication (FSOC) system for multiplexing and demultiplexing multiple polarization channels with a cascade of 3 biaxial crystals, see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…We would like to note that the FSOC system reported in this thesis is not the only technological application of CR. In collaboration with the group of Prof. Edik U. Rafailov at the Aston University (Birmingham), we have shown that the doping elements found in our biaxial crystals can be used to built intracavity lasers with CR patterns [138]. Additionally, due to that for a uniformly polarized input beam there exists a direct link between the intensity distribution of the CR rings and the state of polarization of the input beam, we have demonstrated and patented a single-shot polarimeter based on CR in collaboration with the group of Prof. Juan Campos at the Universitat Autònoma de Barcelona, see Refs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been a renewed interest in the conical refraction (CR) phenomenon ocurring in biaxial crystals, which can also provide different vector beams [11][12][13][14][15][16][17][18][19][20][21][22][23]. In CR, when a focused Gaussian input beam with waist radius w 0 propagates along one of the * Corresponding author: alejandro.turpin@uab.cat optic axes of a biaxial crystal it appears transformed at the focal plane as a pair of concentric and well resolved bright rings split by a dark (Poggendorff) ring of geometrical radius R 0 , as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Another important feature of conical refraction (known as Raman spots) 4 concluding the axial evolution of CR pattern was observed more than a century after the first CR experiments. Although the practical applications of CR has been limited by the difficulties associated with cutting of the biaxial crystals with the necessary precision, a few recent papers report on ultra-efficient CR lasers 5,6 , lasers with CR output from the plane mirror 7 , optical trapping with CR beams 8 , utilization of CR for quantum computing and cryptography 9 and super-resolution microscopy 10 . All these applications attracted our attention to the research of CR of the beams of semiconductor lasers, which are the most compact and efficient sources of radiation but often feature the high value of the beam propagation parameter M 2 .…”
Section: Introductionmentioning
confidence: 99%